2006
DOI: 10.1002/eat.20293
|View full text |Cite
|
Sign up to set email alerts
|

Are there gender differences in core symptoms, temperament, and short-term prospective outcome in anorexia nervosa?

Abstract: Although gender has little effect on the clinical features of anorexia nervosa, the illness runs a more protracted early course in females. Possible mechanisms underlying greater persistence of morbidity in females include sexual dimorphisms in brain neurotransmission, gender differences in attitudes regarding ideal body weight, and anxiety-related personality phenotypes associated with anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
10
40
2
1
Order By: Relevance
“…Most studies on therapy have been conducted in males with Anorexia Nervosa (AN) undergoing inpatient-residential treatment. A Swedish case register study (n ¼ 61) (Lindblad et al, 2006) for example found that the outcome of males with AN admitted for hospital treatment was better than for females which is in agreement with the findings of Strober et al (2006). Also, Deter et al (1998) reported a better psychosocial outcome in men with AN than in women, albeit two male cases died in this cohort.…”
Section: Therapy For Anorexia Nervosa Malessupporting
confidence: 73%
See 1 more Smart Citation
“…Most studies on therapy have been conducted in males with Anorexia Nervosa (AN) undergoing inpatient-residential treatment. A Swedish case register study (n ¼ 61) (Lindblad et al, 2006) for example found that the outcome of males with AN admitted for hospital treatment was better than for females which is in agreement with the findings of Strober et al (2006). Also, Deter et al (1998) reported a better psychosocial outcome in men with AN than in women, albeit two male cases died in this cohort.…”
Section: Therapy For Anorexia Nervosa Malessupporting
confidence: 73%
“…Other studies have however referred to a better (Deter, Kopp, Zipfel, & Herzog, 1998;Lindblad, Lindberg, & Hjern, 2006;Strober et al, 2006) or even a poorer (Oyebode, Boodhoo, & Schapira, 1988) outcome in male patients when compared to females of the same ED diagnosis.…”
Section: Outcome Of Eds Across Gendermentioning
confidence: 97%
“…The markedly higher prevalence of AN among females has encouraged speculation that causative influences may differ between genders. Qualitative observations suggest that, when compared with females, males with AN have more general atypical features such as psychosis or psychotic regression, personality disorder and sexual uncertainty (Ewan, Middleman, & Feldmann, 2014;Fichter & Daser, 1987); for these patients, Strober et al (2006) reported less concern about actual weight. Fichter and Daser (1987) observed that 80% of the males in their study grew up in families that regarded sex as a taboo subject.…”
Section: Stratified Multinomial Analysismentioning
confidence: 97%
“…For instance, it has been shown that men with binge eating disorder have shown greater occurrences of anxiety disorder symptoms than women (Tanofsky et al 1997). It has also been shown that anxiety in men is one of the most consistent predictors of disordered eating (McCabe & Vincent 2003, Strober et al 2006). …”
Section: Anxietymentioning
confidence: 99%